Unified Identity Access Management: A Transformative Framework for Healthcare Security and Efficiency - Srikanth Gurram, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Unified Identity Access Management (IAM) is transforming healthcare security and operational efficiency by addressing critical challenges in digital healthcare environments. As medical institutions rapidly adopt electronic systems, they face growing threats from unauthorized access while simultaneously needing to improve clinical workflows. IAM frameworks provide a comprehensive solution by centralizing identity management across diverse healthcare systems, enabling organizations to implement consistent security policies while reducing authentication burdens for healthcare professionals. This integration significantly enhances regulatory compliance with frameworks like HIPAA and GDPR while supporting streamlined access to critical patient information. Through automation of provisioning processes, healthcare organizations experience substantial reductions in administrative overhead and security vulnerabilities. Furthermore, IAM solutions are vital integration layers between legacy systems and modern platforms, allowing for strategic technological transition without compromising security or disrupting clinical operations. The multi-faceted benefits of unified IAM extend beyond security enhancement to include improved clinical efficiency, patient outcomes, and operational agility, representing a fundamental transformation in healthcare technology management.
Keywords: Identity access management; healthcare security; clinical workflows; regulatory compliance; legacy system integration